2005
DOI: 10.1158/1078-0432.ccr-04-2256
|View full text |Cite
|
Sign up to set email alerts
|

Polysomy 17 in HER-2/neu Status Elaboration in Breast Cancer: Effect on Daily Practice

Abstract: Purpose: To assess the effect of chromosome 17 copy number on HER-2/neu status determination in breast cancers. Experimental Design: HER-2/neu gene copy and chromosome 17 centromere numbers were evaluated on 893 breast carcinomas using double color fluorescence in situ hybridization (FISH). The net and chromosome 17 corrected (ratio) HER-2/neu copy numbers were compared and related to immunohistochemistry done according to the Food and Drug Administration (FDA)^approved scoring system (0, 1+, 2+, and 3+) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
66
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 42 publications
8
66
1
2
Order By: Relevance
“…Therefore, these cases did not fit within the HER2-amplified breast carcinoma category. 21,22 Taken together, a subgroup of borderline (2þ) breast carcinomas represented a majority of the cases with increased CEP17 copy number in our study, and only 13% of the cases showed HER2 gene amplification. This finding is in line with previous studies that confirmed that breast cancers with an equivocal IHC score (2þ) harbored CEP17 polysomy instead of HER2 gene amplification.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…Therefore, these cases did not fit within the HER2-amplified breast carcinoma category. 21,22 Taken together, a subgroup of borderline (2þ) breast carcinomas represented a majority of the cases with increased CEP17 copy number in our study, and only 13% of the cases showed HER2 gene amplification. This finding is in line with previous studies that confirmed that breast cancers with an equivocal IHC score (2þ) harbored CEP17 polysomy instead of HER2 gene amplification.…”
supporting
confidence: 50%
“…21 Our study indicates that determination of HER2 amplification status may show discordant results, depending on whether CEP17 copy number was taken into account. Indeed, more than one-third of the studied cases harboring >6 copies of the HER2 gene did not show HER2 gene amplification (ratio, >2.2).…”
mentioning
confidence: 77%
“…Several investigators have shown that polysomy of chromosome 17 can account for a small subset of breast cancers showing 3 þ levels of HER2 immunostaining but no amplification by FISH when the HER2/chromosome 17 ratio is evaluated. [44][45][46] In the present study, of the 15 cases that were IHC 3 þ and FISH nonamplified, 8 had polysomy of chromosome 17 with HER2/CEP17 ratios that were less than 2. Therefore, a concordance rate of 95% or higher may well be biologically unattainable.…”
Section: Discussionmentioning
confidence: 43%
“…Several investigators have shown that polysomy of chromosome 17 can account for a small subset of breast cancers showing 3 þ levels of HER2 immunostaining but no amplification by FISH when the HER2/chromosome 17 ratio is evaluated. [69][70][71] The new ASCO-CAP guidelines mandate significant changes in HER2 testing in laboratories throughout the United States. As technical handling of tissue continues to be a significant factor in standardization of test quality, the new guidelines mandate fixation in 10% neutral-buffered formalin for a minimum of 6 h and a maximum of 48 h duration.…”
Section: Part 2: Human Epidermal Receptor Protein-2mentioning
confidence: 99%